Rural cultural tourism: An approach to its state of knowledge in Latin America - Mejia Vilchis, Dalia Ibet (2025)
The purpose of this article is to provide an approximation to the current state of knowledge on cultural tourism in rural areas of Latin America, particularly in Mexico, and to highlight its lines of research and theoreticalmethodological scope. Documents published between 2000 and 2024 in national and international scientific databases were analysed. However, the first article was published in 2005, and a set of 46 texts was collected referring to Mexico, Costa Rica, Peru, Ecuador, Brazil, Chile, and Argentina. The informative documentary methodology was used, and an analysis of the discourse was carried out, identifying four lines of research: (i) tourist potentiality, (ii) tourist behaviour, (iii) general theoretical and political reflections, and (iv) magical and touristic villages. The conclusions reflect the scope of research into this topic in Latin America, where emphasis is placed on exploiting its tourist potential rather than formulating explanatory theoretical models.